STUDY ON VISUAL SCENARIOS FOR UNDERSTANDING SOCIAL STRUCTURES, COMMUNITY DYNAMICS, ELDERS’ ROLES AND GENDER INFLUENCES IN THE DIDAYI TRIBE OF MALKANGIRI DISTRICT OF ODISHA - Gudia, Jyotiranjan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Examining the Social life of the Didayi tribe in the Malkangiri district of Odisha, eastern India is the primary objective of this study. The geographical borders of India are distinct from those of other nations. Odisha contains a variety of tribal communities, just as other Indian states. Now, 62 tribal groups have been identified by the Odisha government, accounting for 22.84 percent of the state's total population. Of the 62 tribal communities in Odisha, only 13 are considered to be undeveloped tribes. One of the PVTGs in the Odisha district of Malkangiri is Didayi tribe. They converse in a unique language known as Gahta Saa. There are 8,000 people living in the district alone, which stretches from the Godavari River basins to the Kondakameru mountain range at an elevation of 2000-3500 feet above sea level, according to the 2011 census. They mainly live in 39 villages of four Gram Panchayats under Khairput, Korukonda and the newly transferred Chitrakonda block. The area inhabited by the Didayi tribe has been divided by the government into three parts. For a living, they usually turn to traditional agriculture, animal husbandry, gathering forest goods, fishing and hunting. These tribes have a social way of life different from other tribes because they have their own culture, traditions, social system, customs, festivals, food, drinks, clothes and religion. The writers and current scholars have conducted an intriguing study for their scholarly work. The scholars have utilised source materials collected from both primary and secondary data.